Cover Feature: Aggregation‐Induced Emission (AIE) Fluorophore Exhibits a Highly Ratiometric Fluorescent Response to Zn2+ in vitro and in Human Liver Cancer Cells (Chem. Eur. J. 53/2017). Issue 53 (1st August 2017) - Mehdi, Hassan; Gong, Weitao; Guo, Huimin; Watkinson, Michael; Ma, Hua; Wajahat, Ali; Ning, Guiling
Abstract : A new AIE‐active fluorophore that exhibits a rapid and highly selective ratiometric response to Zn 2+ with a limit of detection (LOD) up to 2.6 nm is reported. Furthermore, the fluorophore was successfully applied in ratiometric imaging of intracellular Zn 2+ in human hepatoma cancer cells by fluorescent confocal microscopy. More information can be found in the Full Paper by W. Gong, M. Watkinson, G. Ning et al. onpage 13067 .